Impact of surgical experience on recurrence and progression after transurethral resection of bladder tumour in non-muscle-invasive bladder cancer. (June 2014) - Jancke, Georg; Rosell, Johan; Jahnson, Staffan
Abstract Objective. This study aimed to evaluate the impact of experience in transurethral resection of bladder tumour (TURBT) on recurrence and progression in primary Ta/T1 urinary bladder cancer. Material and methods. Clinical and pathological characteristics of patients with primary Ta/T1 urinary bladder cancer were recorded prospectively from 1992 to 2007 inclusive. Data on surgeons' experience were categorized as follows: experience by training status (residents or specialists); number of TURBTs performed by each surgeon during the registration period, with cut-off levels at more than 100, more than 150, more than 200, greater than the median and above the third quartile of surgical volume; and lifetime high-volume surgeons (>100 TURBTs). Hazard ratios (HRs) were estimated using Cox regression with 95% confidence intervals (CIs) in multivariate analyses. Results. The analysis included 768 evaluable patients with a median follow-up of 60 months. Recurrence was observed in 478 patients (62%) and progression in 71 (9%). Surgery was performed by residents in 100 cases and specialists in 668, with recurrence in 75 (75%) and 403 (60%) patients, and progression in nine (9%) and 62 (9%), respectively. Surgery performed by specialists was significantly associated with a lower recurrence rate (HR = 0.68, 95% CI 0.53–0.87) but not progression (HR = 0.76, 95% CI 0.37–1.56). Surgical volume had no significant impact on recurrence or progression in any of the analyses at the chosen cut-offs. Conclusions. Surgical experience (specialist/resident) was predictive for recurrence after TURBT for Ta/T1 bladder cancer. Training programmes, checklists and specialist-assisted surgery may shorten the learning curve and improve results.